Orf Disease Following “Eid ul-Adha”: A Rare Cause of Erythema Multiforme - Shahmoradi, Zabihollah (Medknow Publications & Media Pvt Ltd, 2014)
Orf, also known as contagious pustular dermatitis, is an exanthemous disease caused by a parapox virus. It is usually a benign locally self-limiting illness; it can have systemic complication or progressive infected locations can include the finger, hand, arm, and face. Development of erythema multiforme following Orf infection is very rare. In Islamic populations such as those of Iran, Orf can be observed in individuals who are not occupationally involved, but may be in contact with sheep or goats after the Islamic worship as an “Eid ul-Adha.” Here we report an erythema multiforme associated with multiple lesion of Orf disease following the “Eid ul-Adha” in Iranian housewives.